Closing the deal with BPM move your client off the fence and into commitment. - Cameron, David (SOA webservices journal.)
Whether you're in a clothing store, a car dealership, or a bank's online catalog looking for low-interest loans, you're more liable to buy if you get some personal attention. You want someone to answer your questions in real time.